2004
DOI: 10.2188/jea.14.129
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Relationship between an Endothelin-1 Gene Polymorphism (Ala288Ser) and Incidence of Hypertension: A Retrospective Cohort Study among Japanese Workers

Abstract: BACKGROUND: Some case-control association studies revealed the relationship between some endothelin-1 (ET-1) gene polymorphisms and blood pressure. Because no report was available about the relationship between any ET-1 gene polymorphism and incidence of hypertension, we examined the relationship between novel ET-1 gene polymorphism (G862T / Ala288Ser in exon 5) and incidence of hypertension by a retrospective cohort study. METHODS: The subjects were Japanese workers at a company in Shimane Prefectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Several single nucleotide polymorphisms (SNPs) of the genes of preproET‐1, ECE‐1 , CMA, ET A and ET B receptors were identified 42–72 . Some of these SNPs have been investigated in terms of functional relevance and association with cardiovascular ( 1) and noncardiovascular ( 2) phenotypes and/or diseases.…”
Section: Polymorphisms Of Genes Of the Et Systemmentioning
confidence: 99%
“…Several single nucleotide polymorphisms (SNPs) of the genes of preproET‐1, ECE‐1 , CMA, ET A and ET B receptors were identified 42–72 . Some of these SNPs have been investigated in terms of functional relevance and association with cardiovascular ( 1) and noncardiovascular ( 2) phenotypes and/or diseases.…”
Section: Polymorphisms Of Genes Of the Et Systemmentioning
confidence: 99%
“…In addition, within the ET-1 gene, the existence of several polymorphisms has been confirmed, including the C/T substitution located on intron 4; the existence of such a polymorphism provides means for its use as a genetic marker for the examination whether the ET-1 gene is the causative gene of the outbreak of various clinical diseases (9). According to the results of various genetic epidemiological research studies conducted to date, the polymorphisms of the ET-1 gene have been reported to show a relationship with various clinical diseases, including essential hypertension; however, not all studies have presented congruent results (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%